2019
DOI: 10.1371/journal.pone.0225940
|View full text |Cite|
|
Sign up to set email alerts
|

Leisure-time physical activity and sports in the Brazilian population: A social disparity analysis

Abstract: ObjectivesTo estimate the prevalence of leisure-time physical activity (LTPA) or sports in the Brazilian population according to demographic and income variables.MethodsData from 60,202 Brazilian individuals (18 years and over) were analyzed, belonging to the National Health Survey 2013 sample. The prevalence of different modalities of LTPA and sports was estimated according to age, sex, skin color and income. The adjusted prevalence ratios were estimated by Poisson regression.ResultsOf every thousand Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Walking was the most important type of NPA (71%) undertaken by women in Hermosillo, followed distantly by running and cycling. These results are consistent with the findings of other studies in Latin America (Guimarães et al, 2019;Salvo et al, 2017). These activities are performed at a very low pace and for a short time, so most women did not report a significant change in heartbeat and breathing as a result of the exertion (79.7%), and only one third exercised more than two hours per week.…”
Section: Discussionsupporting
confidence: 91%
“…Walking was the most important type of NPA (71%) undertaken by women in Hermosillo, followed distantly by running and cycling. These results are consistent with the findings of other studies in Latin America (Guimarães et al, 2019;Salvo et al, 2017). These activities are performed at a very low pace and for a short time, so most women did not report a significant change in heartbeat and breathing as a result of the exertion (79.7%), and only one third exercised more than two hours per week.…”
Section: Discussionsupporting
confidence: 91%
“…One study has found that the basic infrastructure of essential services can influence both income distribution and health perception in the investigated neighborhood [ 36 ]. Studies have also found an association between social inequality, exercising [ 37 ], access to and intake of food among Brazilians [ 38 ]. Socially disadvantaged individuals were the most underprivileged in these aspects [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found an association between social inequality, exercising [ 37 ], access to and intake of food among Brazilians [ 38 ]. Socially disadvantaged individuals were the most underprivileged in these aspects [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that less favorable economic conditions can hinder access to the practice of LTPA. Furthermore, skin color can be related not only to economic conditions but also to other aspects that may contribute to LTPA disparities, such as aspects related to segregation [ 42 ]. Also, data from the National Health Survey of Brazil showed that less healthy habits are associated with non-white skin color [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%